Melody and the gemini locket - Allen, Elise; Blyton, Enid. (b, 2013)
In the Land of Doubles, Melody takes the lead as the Faraway fairies search for the magical Gemini Locket, but when she comes face to face with her twin, Mel, things go amok until the troll, Tallie, helps them influence his twin, Talon, in a surprising way.
Keywords: Fairies -- Juvenile fiction; Trolls -- Juvenile fiction; Fairies -- Fiction